A systematic review of the evidence relating to disclosure of psychological distress by mental health professionals within the workplace. Issue 9 (5th March 2022) - Zamir, Aliya; Tickle, Anna; Sabin‐Farrell, Rachel
Abstract: Objective: To systematically review evidence regarding prevalence and choices of disclosure of psychological distress, by mental health professionals within the workplace. Methods: Six databases were searched in June 2020. Studies were included if they were published in English language and included empirical quantitative, qualitative or mixed‐methods data. Studies were excluded if they focused on general healthcare professionals or the general population, or on stress or physical health problems. Study quality was assessed using the Mixed Methods Quality Appraisal tool. Results: Nine studies, with a total of 1891 participants, were included. Study quality varied, with studies generally reporting descriptive surveys using hypothetical disclosure scenarios. Distress was often conceptualized in psychiatric terms. These limitations mean conclusions should be treated with caution. Individuals were less likely to disclose in work and had negative experiences of doing so compared to social circles. Fear of stigma inhibited disclosure. There were differing levels of disclosure relating to recipient, trust, quality of supervision, how distress was conceptualized, and type of problem. Disclosure was experienced by some as valuable. Conclusion: There is a need for further research, which addresses the nuanced complexities surrounding disclosure choices for mental health professionals.